IMPACT OF BREASTFEEDING ON THE INTELLIGENCE QUOTIENT OF THE CHILDREN (Asian Journal of Medical Research and Health Sciences, 2026)
Background: It is well known that breastfeeding is an important influence on optimal physical, cognitive and emotional development in early childhood. Breast milk contains all the nutrients needed for brain maturation, long-chain polyunsaturated fatty acids, immunological components, and bioactive substances which are beneficial to brain function. Worldwide, it is believed that breastfeeding is linked to an increased intelligence quotient (IQ), however, this has not been sufficiently studied in many low and middle income countries. It is crucial to grasp this linkage in order to design public health policies, parent counseling, and early childhood development interventions. This study was designed to examine the association between breastfeeding and IQ of children. Study design: Comparative cross-sectional study Place and Duration of Study: This study was conducted at Hamdard University of Medicine and Dentistry Karachi from April 2025 to April 2026 Methodology: The study employed a sample of 88 children who had been recruited using non‐probability convenience sampling technique on the basis of predetermined inclusion and exclusion criteria. Ethical Approval and informed consent was taken before data collection. Infants were classified as exclusively breastfed and formula fed. IQ was measured on the Wechsler Intelligence Scale for Children (WISC) which was administered by trained assessors under standardised conditions. Descriptive and inferential statistics were used in analyzing the data. Associations between feeding type, breastfeeding duration and the IQ categories were tested using the chi-square test. A p‑value